DEVELOPING E-MODULE BASED ON RIAU MALAY CULTURE AS TEACHING MATERIAL FOR DESCRIPTIVE TEXT AT SMPN 17 PEKANBARU - Azura, Ayu; Jismulatif, Jismulatif; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study was intended to develop an electronic module based on Riau’s local wisdom as teaching material for descriptive text and to discover its level of validity. Thus, this study applied the Research and Development (R&D) using the 4D model introduced by Thiagarajan et al. (1974). The data of this study were collected through an interview with an English teacher at SMPN 17 Pekanbaru, the validation sheet by media and material experts, and responses questionnaires by teacher and students. The results of this study show that the validity results obtained from the media expert is 85.71% which categorized as Valid, and the validity results from the material expert is 98.80% which categorized as Highly Valid. The results of the teacher response questionnaire showed 98.52% which was categorized as Very Practical, while the results of the student response questionnaire received 76.21% which was categorized as Practical. Therefore, the e-module was declared valid and feasible for seventh grade students at SMPN 17 Pekanbaru. The use of the e-module can serve an alternative teaching material and help improve students’ understanding of descriptive text, as well as broaden their understanding and appreciation of local culture, especially Malay buildings.Keywords: E-module, Riau Malay Culture, Descriptive Text